1997
DOI: 10.1002/mrm.1910370230
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl alcohol cryogel: An ideal phantom material for MR studies of arterial flow and elasticity

Abstract: The authors present a unique application of polyvinyl alcohol (PVA) cryogel as an anthropomorphic, elastic, vascular phantom material that can be used in MR imaging. The composition consists of two nontoxic ingredients: water and PVA. The biomechanical and MR properties can be adjusted to be similar to those of excised porcine aortas by varying the number of freeze-thaw cycles to which the PVA solution is exposed. The authors present the T1, T2, shrinkage, and tensile properties of PVA cryogel tubes as a funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
191
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 262 publications
(206 citation statements)
references
References 24 publications
10
191
0
1
Order By: Relevance
“…This may suggest that the PVA-C material was approaching saturation point of the cryogel in terms of intermolecular cross-linking. This effect has been observed elsewhere (Chu and Rutt, 1997) and places an upper limit on Young's elastic moduli available for a given concentration of cryogel. The Young's elastic modulus values, which ranged from 19 to 165 kPa in the current study, are similar to those obtained by Duboeuf et al (2007) for 10 % PVA-C concentration.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…This may suggest that the PVA-C material was approaching saturation point of the cryogel in terms of intermolecular cross-linking. This effect has been observed elsewhere (Chu and Rutt, 1997) and places an upper limit on Young's elastic moduli available for a given concentration of cryogel. The Young's elastic modulus values, which ranged from 19 to 165 kPa in the current study, are similar to those obtained by Duboeuf et al (2007) for 10 % PVA-C concentration.…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, bacterial growth appeared on a number of PVA-C samples which did not contain any anti-bacterial agent after several days. Chu and Rutt (1997) used an anti-bacterial agent in their PVA-C samples and indicated that the agent changed the MR relaxometry properties of their samples; however, they did not quantify this change. The use of Benzalknonium Chloride (BC) in the current study stemmed from its use in a previous study, where it was observed to increase the lifetime of a TMM (Teirlinck et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations